Inhibitory Potential of Black Seed (Nigella sativa L.) Bioactive Compounds Towards Main Protease of SARS-CoV-2: In Silico Study - Ferdian, Pamungkas Rizki; Elfirta, Rizki Rabeca; Emilia, Qori; Ikhwani, Azra Zahrah Nadhirah (Annales Bogorienses, 2020)
COVID-19, caused by SARS-CoV-2, has become a massive worldwide concern of the 21st century. One potential strategy to block the biochemical pathway of SARS-CoV-2 was by inhibiting the main protease (Mpro), which is a key enzyme on viral replication. Black seed (Nigella sativa L.) has a long history for its use as a traditional medicine. Therefore, we hypothesised that the black seed contains numerous active compounds that could potentially confer inhibitory activity against SARS-CoV-2 viral Mpro. In this study, 24 active compounds from black seed were tested. Compounds were screened using Lipinski's Rules and admetSAR, then docked to viral Mpro 7BQY by AutoDockTools-1.5.6 and AutoDock Vina using a site directed docking approach resulting in affinity energy (∆G) and binding data. We found that the most potential active compound of N. sativa is 3-[(4-Methylphenyl)sulfanyl]-1,3-diphenyl-1-propanone, since its affinity energy was -7.6 kCal.mol-1. Its similarity to N3 inhibitor based on Ligplot analysis and DS were 86.7% and 76.19%, respectively, and the occupancy on binding site based on Ligplot analysis and DS were 90.91% and 81.82%, respectively. These findings can be used as a starting point for further investigation using in vitro and in vivo studies.